ANALYSIS OF ELECTROENCEPHALOGRAMS RHYTHMS BY MEANS OF NONLINEAR OPERATOR TEAGER-KAISER - A. O. Kozmidiadi; A. P. Kluev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of the development and application of methods for solution of applied tasks of analysis of the rhythmic activity of the electroencephalogram based on the nonlinear operator.